On the burst strength capacity of an aging subsea gas pipeline - Bin Mohd, M.H. (American Society of Mechanical Engineers (ASME), 2014)
Precise evaluation of the performance of aging structures is particularly essential in the oil and gas industry, where inaccurate predictions of structural performance may lead to significantly hazardous consequences. It is also important to accurately predict the corrosion behavior of pipeline structures used in the production of gas in subsea areas. The effects of pipeline failure due to a significant reduction in burst strength make it hard for pipeline operators to maintain pipeline serviceability. Therefore, the serviceability of ongoing subsea gas pipelines should be assessed according to their burst strength capacities, which should not exceed the maximum allowable operating pressure (MAOP). In this study, the critical part of the corrosion along a 2.4 km pipeline was evaluated using two approaches: an empirical design codes formula and ANSYS numerical analysis. The future integrity of the aging pipeline was then assessed to predict its remaining years of service. The results and outcomes of this study will be useful in evaluating pipeline integrity and predicting the remaining service life of aging pipeline structures. Â© 2014 by ASME.